Evaluation of the Blend in Bagasse Ash-Quarry Dust Stabilization of Expansive Soils for Road Pavement. - Tumwesigire, Osbert (Kabale University, 2023)
Expansive soils are encountered in many construction sites and exhibit poor engineering properties. Traditional stabilizers like cement, lime and others have been efficient and effective in soil stabilization but their rising costs and negative impact to the environment has led to research into bagasse ash and quarry dust to be used as alternatives in soil stabilization. The study investigated the effect of bagasse ash – quarry dust blend stabilization on engineering properties of expansive soil in the ratios of 80%N.S+15%B.A+5%Q.D, 60%N.S+25%B.A+15%Q.D, 40%N.S+35%B.A+25%Q.D. The study covered the grading test, Atterberg limits, compaction test California bearing ratio and unconfined compressive strength. The preliminary investigation shows that the soil belongs to A-7-5 class of soil in the AASHTO Soil classification system and unified soil classification system. The values of UCS increased from 367.8 to 737.9Kpa at 14days of curing for 80%N.S +15%B.A +5%Q.D which indicated that the strength increases with age. From the results it was observed that an A-7-5 (4) expansive soil stabilized with 80%N.S +15%B.A +5%Q.D content is suitable for use as a sub base course material in road pavement construction.